Review of Diesel Particulate Matter Control Methods in Underground Mines - Chang, Ping; Xu, Guang (Springer, 2019)
Diesel-powered equipment is widely used in the mining industry due to its superb performance, cost-effectiveness, efficiency as well as durability. However, there is a potential for miners in underground mines to be overexposed to high diesel particulate matter (DPM) concentrations with the increasing use of diesel engines. In 2012, the International Agency for Research on Cancer (IARC) classified DPM as a carcinogen to humans (group 1) based on sufficient evidence from animal and epidemiological studies. Regulations and control methods have been developed to minimize DPM health hazard in underground mines. This pa-per firstly reviewed the adverse health effects of DPM on humans based on re-lated animal and epidemiological studies. Findings indicated that both short-term and long-term exposure to high concentrations of DPM have adverse impacts (acute irritation, asthma, cough, light-headedness, lung cancer, etc.) on humans, and a recommended limit of DPM concentration (0.1 mg/m3, measured as ele-ment carbon) should be established to help reduce miners’ risk of lung cancer. The effects of DPM control methods were also evaluated, which include source controls and exposure controls. Finally, an optimum DPM controlling strategy was obtained to lower DPM concentrations and provide a safe and healthy work-ing environment for miners.